2016
DOI: 10.1063/1.4961205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing ambient on anisotropic retraction of film edges during solid-state dewetting of thin single crystal films

Abstract: During solid-state dewetting of thin single crystal films, film edges retract at a rate that is strongly dependent on their crystallographic orientations. Edges with kinetically stable in-plane orientations remain straight as they retract, while those with other in-plane orientations develop in-plane facets as they retract. Kinetically stable edges have retraction rates that are lower than edges with other orientations and thus determine the shape of the natural holes that form during solid-state dewetting. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The edge alignment along the particular directions can be understood in terms of the surface energy anisotropy of the film material, and it has also been demonstrated that they can be tuned by varying the annealing ambient [78]. It has been suggested that surface reconstruction by oxygen adsorption can also affect the hole shapes in Ni (100) and Ni (110) films as indicated by low-energy electron diffraction analysis [79]. Because of this shape anisotropy in nucleated holes, single-crystal films dewet into more regular morphologies compared to polycrystalline or liquid films.…”
Section: Nucleation and Growth Of Holesmentioning
confidence: 99%
“…The edge alignment along the particular directions can be understood in terms of the surface energy anisotropy of the film material, and it has also been demonstrated that they can be tuned by varying the annealing ambient [78]. It has been suggested that surface reconstruction by oxygen adsorption can also affect the hole shapes in Ni (100) and Ni (110) films as indicated by low-energy electron diffraction analysis [79]. Because of this shape anisotropy in nucleated holes, single-crystal films dewet into more regular morphologies compared to polycrystalline or liquid films.…”
Section: Nucleation and Growth Of Holesmentioning
confidence: 99%
“…32 Differences in thermal dewetting atmosphere have been shown to influence the dewetting behavior and the morphology evolution of metal thin films. 33,36,37 Particularly, in their study on the effect of oxygen adsorption on the morphological evolution of Ag films on Si substrates, Ye et al 35 have shown that oxygen enhances the dewetting rate of Ag thin films which they attribute to the decrease in the activation barrier for the surface diffusion of Ag atoms due to oxygen adsorption. With the reduced activation energy, surface diffusion could take place more easily, leading to a faster dewetting process, as thermal dewetting is a solid-state dewetting process driven by surface diffusion.…”
Section: Effect Of Residual Oxygen On the Morphology Evolution In The...mentioning
confidence: 99%
“…Geissler et al reported the effect of H 2 pressure on the size of Ni NPs formed during thermal dewetting of Ni films on SiO 2 (25 nm)/Si substrates, where the NP size was seen to increase along with a decrease in the NP number density when the H 2 pressure increased. The effect of annealing ambient on the equilibrium crystal shape of Ni nanoparticles formed during solid-state thermal dewetting has also been reported. Adsorption of oxygen and hydrogen on metal surfaces has a significant impact on both the surface energy anisotropy and the surface diffusion anisotropy, leading to anisotropic retraction of film edges during thermal annealing and eventually the equilibrium crystal shape. The effect of ambient conditions on the size and shape of Pt NPs in the solid-state thermal dewetting of Pt thin films has been much less studied.…”
Section: Introductionmentioning
confidence: 99%